2008
DOI: 10.1038/sj.bjp.0707599
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac capsaicin‐sensitive sensory nerves regulate myocardial relaxation via S‐nitrosylation of SERCA: role of peroxynitrite

Abstract: Background and purpose: Sensory neuropathy develops in the presence of cardiovascular risk factors (e.g. diabetes, dyslipidemia), but its pathological consequences in the heart are unclear. We have previously shown that systemic sensory chemodenervation by capsaicin leads to impaired myocardial relaxation and diminished cardiac nitric oxide (NO) content. Here we examined the mechanism of diminished NO formation and if it may lead to a reduction of peroxynitrite (ONOO À )-induced S-nitrosylation of sarcoendopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…A plausible explanation is that while MMP-9 is an abundant enzyme in different cells and tissues including macrophages and leukocytes, MMP-2 is an intracellular enzyme mainly in contractile tissues that can be activated and released e.g. due to acute myocardial ischemia/reperfusion and infarction [8,[21][22][23][24], however, our CAD patient population did not have severe ischemia at the time of tissue sampling, therefore, MMP-2 activation and release can be less sensitively detected in the serum.…”
Section: Serum Nitrotyrosine Correlates With Mmp Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible explanation is that while MMP-9 is an abundant enzyme in different cells and tissues including macrophages and leukocytes, MMP-2 is an intracellular enzyme mainly in contractile tissues that can be activated and released e.g. due to acute myocardial ischemia/reperfusion and infarction [8,[21][22][23][24], however, our CAD patient population did not have severe ischemia at the time of tissue sampling, therefore, MMP-2 activation and release can be less sensitively detected in the serum.…”
Section: Serum Nitrotyrosine Correlates With Mmp Activitymentioning
confidence: 99%
“…The main effector of nitro-oxidative stress is peroxynitrite, which may activate several enzymes including MMPs via S-nitrosylation/S-glutathiolation of their tyrosine and/or cystein residues [7,8]. Furthermore, peroxynitrite nitrates free tyrosine residues to form nitrotyrosine, which is a widely used marker for peroxynitrite generation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike RyR, studies have not investigated if NOS1 is able to directly modulate SERCA activity. However, a study demonstrated that SERCA is S-nitrosylated (14), but the NO source responsible for this post-translational modification was not investigated. It has also been reported that nitroxyl (the 1 electron reduction product of NO) is able to modify SERCA via S-glutathiolation of cysteine674 (102).…”
Section: Sr Camentioning
confidence: 99%
“…51,[53][54][55][56][57]. However, excess of NO in the presence of the co-existing free radicals have detrimental effect on cell survival.…”
Section: +mentioning
confidence: 99%